Subject Learning Options Analysis - Balikova, Vita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the article the author considers the problem of the reducingof number of surrendered individual works by educational subject.Analyzing the possible causes of this problem, the author of the workexplores the needs of age of the students, didactic principles, which aremainly used by the teacher in teaching practice. The author of thisarticle studies the impact of new technology on the thinking of youngpeople as well. At result of research the hypothesis of individual workdivision into smaller parts is proposed and tested. This article presentsthe results of testing this hypothesis.